1995
DOI: 10.1163/22941932-90001424
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Growth Dynamics in Tropical Trees a Review

Abstract: Cambial dormancy and annual rings in tropical trees are induced by annually occurring dry periods or flooding. Growth periodicity is indicated by the leaf fall behaviour and is connected with an annual periodicity of shoot elongation. Changes in stem diameter are measured with a dendrometer or by measurable differences in the electrical resistance of the cambium. Dendrochronological methods applied to carefully prepared samples can serve as proof of the annual periodicity of growth zones. For this purpose the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
247
1
69

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(327 citation statements)
references
References 20 publications
10
247
1
69
Order By: Relevance
“…In the tropics, periods of the drought and rain may produce differential growth, particularly in regions of marked seasonality (Costa et al 2006). This annual dry season, with lower monthly rainfall, may lead to the formation of annual rings in tropical trees (Worbes 1995). The marked seasonality at GES (Silva & Nascimento 2001;Villela et al 2006), likely explains the presence of distinct growth rings in A. pickelii growing there.…”
Section: Discussionmentioning
confidence: 98%
“…In the tropics, periods of the drought and rain may produce differential growth, particularly in regions of marked seasonality (Costa et al 2006). This annual dry season, with lower monthly rainfall, may lead to the formation of annual rings in tropical trees (Worbes 1995). The marked seasonality at GES (Silva & Nascimento 2001;Villela et al 2006), likely explains the presence of distinct growth rings in A. pickelii growing there.…”
Section: Discussionmentioning
confidence: 98%
“…Segundo Worbes (1995), para espécies de regiões tropicais, uma estação seca com duração de dois a três meses no ano, com precipitação menor que 60 mm é condição ambiental necessária para que as espécies formem camadas de crescimento em seu lenho. O fato da região de estudo apresentar uma estação seca anual com a duração de cinco meses, com precipitação em torno de 38 a 89 mm neste período, pode estar relacionada à formação de camadas de crescimento nesta espécie.…”
Section: Discussionunclassified
“…3,801y, with a standard deviation of 61.6y (Table I). (Worbes 1995). The seasonal climate with fi ve arid months in the study area may be responsible for the growth rings found in Jacaranda decurrens, but further fi eld and wood anatomy studies shall be necessary to demonstrate this.…”
Section: Resultsmentioning
confidence: 93%